Performance Measurement Analysis of Bank 9 Jambi Sutomo Branch using the Balanced Scorecard Method - Azhari, Tri Agil; Sam, Iskandar; Jumaili, Salman (Formosa Journal of Applied Sciences, 2024)
This research aims to analyze the performance measurement of Bank 9 Jambi Sutomo Branch using the Balanced Scorecard method on company performance. The data obtained is primary data and secondary data from PT Bank 9 Jambi Sutomo Branch in 2020, 2021 and 2022. The samples in this study were 48 respondents. The type of research used is descriptive research, with non-statistical qualitative and quantitative research techniques. The sampling method used was simple random sampling. The data quality test used is the validity test, reliability test, and frequency distribution of questionnaire statements.Bank 9 Jambi uses Key Performance Indicators (KPI) to improve company performance. The results of this research are the overall performance of PT Bank 9 Jambi Sutomo Branch in 2020-2022 using the Balanced Scorecard method in the "very good" category.